ANALISIS PERAN TARI DALAM MENGEMBANGKAN KETERAMPILAN SOSIAL ANAK - Lubis, Hilda Zahra; Roaina, Lia; Lubis, Nur Asiah; Amarisa, Yassinta (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to analyze the role of dance in developing children's social skills at Anline Kindergarten. Social skills are an important component in early childhood development which includes the ability to interact, communicate, work together and manage emotions. The research approach used is qualitative with descriptive methods. Data was collected through observation, interviews and documentation. Data analysis uses thematic analysis techniques to identify main themes from the results of interviews and observations. The subjects of this research were teachers at Anline Kindergarten. The research results show that the Batak Tor-Tor dance is effective in developing children's social and emotional skills. Through dance movements, children learn to express their emotions, which helps them better understand and manage those emotions. Group dance activities provide opportunities for interaction with peers, which strengthens cooperation, mutual communication, and empathy. Dance also teaches discipline, responsibility, and self-confidence as children learn moves and perform in front of others. Children who initially feel shy become more confident and motivated when supported by their friends. The experience of dancing together makes this activity more fun and meaningful, so that children feel more enthusiastic and eager to learn. The strategy for implementing the Tor-Tor Batak dance is carried out in stages according to the child's abilities and is carried out repeatedly so that the information is stored in long-term memory. Dance practice is held regularly every Friday and additional practice is held after school. Teachers use YouTube guides to practice dance moves, pay attention to children's facial expressions, and encourage them to always smile while dancing. With proper guidance, children become more disciplined and confident in their performance. Apart from that, the strategy for implementing the Batak tor-tor dance carried out by Anline Kindergarten in developing children's social-emotional abilities is Learning Dance Movements and Techniques, Collaboration and Social Interaction, Evaluation and Monitoring Progress, and Integration with the Educational Curriculum.